Understanding mandatory IS use behavior: How outcome expectations affect conative IS use. Issue 1 (February 2018) - Kwahk, Kee-Young; Ahn, Hyunchul; Ryu, Young U.
Highlights: Successful implementation of standardized enterprise information systems is often a challenging task. We examine the effects of outcome expectations on information systems use activity from the viewpoint of social cognitive theory. We propose a new surrogate variable, called "conative use" for system use activity in the mandatory use context. The empirical results reveal that conative use is positively affected by outcome expectations. The findings of the study imply that the appropriate management of expectations may promote enterprise system use behavior in the mandatory use context. Abstract: Implementing enterprise systems (ES) suffers from a high failure rate despite their promised benefits. A commonly cited reason for ES implementation failures in the context of mandatory use is end users' unwillingness to adopt or use systems or their sabotage thereof. Considering that expectations toward using newly implemented systems may promote positive user behavior, we examine the effects of outcome expectations on information systems (IS) use activity from the viewpoint of social cognitive theory. In addition, we propose a new surrogate variable for IS use activity in the mandatory use context, conative IS use, which is conceptualized as a second-order aggregate construct comprising three dimensions: immersion, reinvention, and learning. Conative IS use here refers to IS use that is proactively motivated by intentional and personal causes. The empirical results, based on data collected from 208 ES users, are found to support the conceptualization of the proposed variable. They also reveal that conative IS use is positively affected by outcome expectations. The findings of this study thus imply that the appropriate management of expectations may promote IS use behavior in the mandatory use context.